GAMBARAN PERAN PERAWAT DALAM PENCEGAHAN DEKUBITUS DI BANGSAL PENYAKIT DALAM RUMAH SAKIT DI YOGYAKARTA - Nofiyanto, Muhamat; Ivana, Erna (Media Ilmu Kesehatan, 2018)
Background : Decubitus prevention need the knowledge, attitude, motivation, and behavior of nurses. Objective : To identify the description of nurses roleâs in decubitus prevention in Internal medicine ward of hospital in Yogya. Method : This was a descriptive design by using cross sectional time approach. The number of samples was 15 respondents selected through total sampling technique. The analysis applied descriptive statistic. Result : The majority of nurses had positive roleâs in decubitus prevention as many as 10 respondents (66.7%), the nurses roleâs according to some characteristics were as follows; The nurses role in the assessment on decubitus risk factor was in good category as many as 9 respondents (60.0%), the nurses role in skin care for patients was in good category as many as 9 respondents (60.0%), the nurses role in patients nutritional status enhancement was in good category as many as 10 respondents (66.7%), the nurses role in support surface was in sufficient category as many as 12 respondents (80.0%), and the nurses role in providing education was in good category as many as 13 respondents (86.7%). Conclusion : The nurses roleâs in decubitus prevention in internal medicine ward of hospital in Yogya is in good category.   Keywords : Decubitus prevention, Nurses roleâs,Positive roleâs